(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In the present work results of researches of zooplanktonic community during 2008-2010 with the account taksonomy structure and distribution in reservoirs Ijr-Majtansky systems of delta of the river are stated Or. In interannual aspect have been calculated an information index of a specific variety on Shennonu and an index of specific similarity on Serensenu.